Perception and Awareness of Diabetes Mellites and Diabetes Ketoacidosis among the General Population in Sudair Area, Saudi Arabia - Yousef A. Alanazi; Bandar M. B. Alsaadoon; Talal M. A. Alanazi; Abdulaziz M. A. Alanazi; Sultan M. B. Alsaadoon; Majeed G. I. Alanazi; Abdulrahman N. N. Almutairi; Khalid F. Alanazi; Riyaz A. Shaik; Elsadig Y. Mohamed (Journal of Pharmacy and Bioallied Sciences)
Background: This study was carried out to assess the level of knowledge and awareness of diabetes and DKA among the general population in the Sudair area of Saudi Arabia. Methods: This cross-sectional study was conducted among the individuals of Sudair area, Saudi Arabia (both Saudi and non-Saudi). The inclusion criteria were individuals who live in Sudair area of both gender and older than 18 years of age. The data will be collected by filling out a pre-designed online questionnaire that has choice answers. Data were analyzed by using SPSS version 24 and presented in tables. Results: There were 709 people who participated in the study; majority of the participants were educated with 368 (51.9%) being University passed out. The majority of the older people believed that diabetic ketoacidosis is dangerous and may cause death. (P < 0.05). People aged less than 30 preferred calling an ambulance immediately 31 (46.9%) rather than taking them to the emergency room when asked about their opinion on a situation if one of their relatives or friends is afflicted with acidity in the blood. (P < 0.05). Conclusion: Awareness of diabetic ketoacidosis (DKA) is low in the Sudair area, though higher among older, more educated, and married individuals. Targeted, multi-channel educational efforts and strong collaboration among healthcare providers, community leaders, and educational institutions are essential to improve understanding and reduce DKA-related health risks.